Heat-shock and methyl-jasmonate: The cultivar-specific responses of pepper plants - Otálora, Ginés; Piñero, María Carmen; Collado-González, Jacinta; Gálvez, Amparo; López-Marín, Josefa; del Amor, Francisco M. (Frontiers in Plant Science, 2022)
Frequency, intensity and duration heat-related events have profound implications for future food supply through effects on plant growth and development. This concern needs effective and urgent mitigation tools. However, the effectiveness of potential solutions may decrease according to the specific cultivar response rather consider at specie level. The metyl-jasmonates are essential cellular regulators which are involved in pivotal plant development processes and related to confer protection to heat shock. Thus, our aim was to study the response of three pepper cultivars, Agio (Hungarian type), Basque (Chilli type), and Loreto (Lamuyo type), subjected to heat shock (40 °C/72 h) and foliarly-sprayed with methyl-jasmonate (MeJa; 100 µmol), and the effects on several physiological traits. Our results show that despite the important differential impact of heat shock caused on each cultivar, MeJa application did not affect gas exchange, chlorophyll A concentration or efficiency of the photosystem in these cultivars. However, P concentration was reduced when MeJa was applied to Basque chilli, and a significant effect on leaf carbohydrates concentration was observed for Agio and Loreto. Moreover, Agio was the only cultivar in which the amino-acid profile was affected by MeJa under heat shock. Under that condition, putrescine increased for all cultivars, whist the effect of MeJa was only observed for spermine and histamine for Agio and Loreto. Thus, the results indicated that the ameliorative impact of MeJa on this stressor was clearly influenced by cultivar, revealing specific traits. Thus, these results could be used as valuable tools for the characterization of this intraspecific tolerance to heat shock during the vegetative growth stage of pepper